El patrocinio en las familias judiciales. Sobre las carreras judiciales en los tribunales cordobeses del siglo XX / Sponsorship inside judicial families. About the judicial careers in Cordoba’s courts in the 20th century ((En)clave Comahue. Revista Patagónica de Estudios Sociales, 2019)
Este artículo se concentra en los modos de reclutamiento de integrantes del Poder Judicial de Córdoba en las décadas finales del siglo XX. A partir de la noción de patrocinio, transformamos la categoría “nativa” familia judicial en una conceptualización, para describir una trama de relaciones de inter-conocidos que resulta definitoria en las carreras judiciales. ABSTRACTThis article focuses on the ways the judiciary of Córdoba recruited members in the final decades of the 20th century. We use the notion of sponsorship to turn the “native” category judicial family into a concept that describes the interweaving relationships among acquaintances, which is the defining feature in judicial careers.